A new Scaphoideini leafhopper genus from China (Hemiptera: Cicadellidae: Deltocephalinae), with description of two new species - Fang, Yongqin; Xing, Jichun (Zootaxa, 2019)
A new genus of the tribe Scaphoideini from China, Changbaninus gen. nov., including two new species: Changbaninus furcatus sp. nov. (type species) and Changbaninus pleiospicules sp. nov. are described and illustrated, and a key to species is provided. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).